Selendang Siti Rugayah: A Spiritual Hermeneutics Reading: (Komik Selendang Siti Rugayah: Suatu Bacaan Hermeneutik Kerohanian) (Malay Literature, 2020)
Rejabhad is more popularly known as Malaysia's "king of cartoons". His works stand out because they provide the opportunity for researchers to analyse them from the angles of visual design and text. Scholarly research in the past has tended only to look at the superficial level of comics. However, those of Rejabhad deserve closer analysis to uncover their meaning on both their superficial and deeper levels. This is important in order to completely understand the meaning of these cartoons and the personality of their creator. This study focuses on Rejabhad's Selendang Siti Rugayah [Siti Rugayah's Shawl] (1997). The methodology employed in this research is a qualitative one, involving analysis of the literal aspects of the visual and textual elements to glean the obvious meaning of this work. A spiritual hermeneutics reading or 'takwil method' is applied to obtain the deeper/spiritual meaning of this comic. The findings of this research enable readers to gain a greater understanding about the deeper meanings of the work and the personality of the writer. The spiritual hermeneutic reading is a new way for exploring works and changing opinions concerning the ability and creativity of Malay comic-book writers, especially Rejabhad, whose works were hitherto appreciated and understood solely on a superficial level.Keywords: sequential art, comics, interpretation, hermeneutics, spiritual hermeneutics, deep meaning, personality